MANAJEMEN PASOKAN DAN PENGADAAN ELEKTRONIK: MENCIPTAKAN NILAI TAMBAH DALAM RANTAI PASOKAN - Joko Triono (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
Increased attention to supply chain management creates a greater focus on supply management links in the supply chain. This focus will become more intense as companies continue to adopt electronic procurement strategies to increase the competitive advantage of the Internet. Supply managers need to understand the impact of technology and gain competence in making business cases for electronic procurement, the implication is very deep for industrial marketers.